Mutant p53K120R expression enables a partial capacity to modulate metabolism - Monti, Paola; Ravera, Silvia; Speciale, Andrea; Velkova, Irena; Foggetti, Giorgia; Degan, Paolo; Fronza, Gilberto; Menichini, Paola (Frontiers in Genetics, 2022)
The TP53 tumor suppressor gene is one of the most studied gene in virtue of its ability to prevent cancer development by regulating apoptosis, cell cycle arrest, DNA repair, autophagy and senescence. Furthermore, the modulation of metabolism by P53 is fundamental for tumor suppressor activity. Studies in mouse models showed that mice carrying TP53 mutations affecting the acetylation in the DNA binding domain still retain the ability to transactivate genes involved in metabolism. Noteworthy, mice expressing the triple 3KR or the single K117R mutant do not show early on-set tumor development in contrast to TP53-/- mice. Interestingly, the mouse K117R mutation corresponds to the human tumor-derived K120R modification, which abrogates P53-dependent activation of apoptosis without affecting growth arrest. In this study, we investigated the property of the human P53 K120R mutant in the regulation of metabolism by analyzing the transcriptional specificity in yeast- and mammalian-based reporter assays, the metabolic phenotype associated to its expression in colon cancer HCT116TP53-/- cells and the induction of P53 targets and proteins involved in the antioxidant response. These properties were analyzed in comparison to wild type P53 protein, the human triple mutant corresponding to mouse 3KR and the cancer hot-spot R273H mutant. We confirm the selective functionality of P53 K120R mutant, which shows a transcriptional activity on cell cycle arrest but not on apoptotic targets. Interestingly, this mutant shows a partial transactivation activity on p53 response element belonging to the metabolic target TIGAR. Moreover, we observe a significant uncoupling between oxygen consumption and ATP production associated with higher lipid peroxidation level in all P53 mutants carrying cells with respect to wild type P53 expressing cells. Noteworthy, in the absence of a pro-oxidative challenge, cells expressing K120R mutant retain a partial capacity to modulate glucose metabolism, limiting lipid peroxidation with respect to the other P53 mutants carrying cells. Lastly, especially in presence of human 3KR mutant, a high expression of proteins involved in the antioxidant response is found. However, this response does not avoid the increased lipid peroxidation, confirming that only wild type P53 is able to completely counteract the oxidative stress and relative damages.